Blockchain-based high transparent PKI authentication protocol - Liquan CHEN; Xiao LI; Zheyi YANG; Sijie QIAN (网络与信息安全学报)
The public key infrastructure (PKI), as an significant component of the current Internet security infrastructure, guarantees the information transmission with the necessary authenticity, integrity, confidentiality and non-repudiation.However, the existing PKI also has shortcomings of excessive power of certification authority and difficulties in revoking and querying.Blockchain can be used to solve those problems by leveraging its advantages, such as decentralization, high transparency and flat structure.Furthermore, the ability and efficiency of the entire Internet to establish trust relationships may be improved.The transparent public key infrastructure (PKI) certification protocol based on the blockchain was proposed.The TS-PBFT algorithm was designed in the proposed protocol by adopting the threshold signature technology to the Practical Byzantine fault tolerance (PBFT) algorithm.The TS-PBFT algorithm reduced the communication overhead via reducing the communication complexity, strengthened the supervision via introducing external monitoring mechanism in the master node election of the view change protocol, and also improved the performance of the consensus mechanism via adding a batch processing mechanism.Moreover, a transparent blockchain-based PKI certification protocol was designed.The proposed protocol increased the security of certificate revocation and query, it also improved the efficiency of the certificate query by the introduction of counting bloom filters.Besides, the proposed protocol added audit function into the certificate lifecycle management.Accordingly, it can supervise the behavior of the certificate authority (CA), prompt it to improve security standards, and then achieve the purpose of limiting its authority.According to the security analysis and efficiency experiments, the proposed protocol was equipped with security properties, such as the resistance to spoofing certificate application attacks, and it achieved the best performance on TLS/SSL handshake time compared with existing PKI protocols.